Ecologia alimentar de pequenos mamíferos de áreas de cerrado no Sudeste do Brasil - Ramos, Vanessa do Nascimento (2007)
The herbivorous mammals in the Neotropics has been studied focusing on larger frugivorous species. However, small rodents and marsupials can perform the role of important selective agents by their trophic relationships. The objectives of this work were to describe the diet of some small mammals in natural remnants of Cerrado, to verify the existence of seasonal variation in the use of food resources and in the morphology of digestive tract, to asses the importance of invertebrates and plants in diet of the studied species trying to know the potential effect of mammals on the local resource communities. The species analyzed were Calomys tener (Rodentia, Cricetidae), Necromys lasiurus (Rodentia, Cricetidae), Lutreolina crassicaudata (Didelphimorphia, Didelphidae) and Gracilianus agilis (Didelphimorphia, Marmosidae). The analyzed specimens belong to mammal collection of Universidade Federal de Uberlândia and were collected in natural remnants of Cerrado in Minas Gerais state. Food habits were studied by the analyses of food remains found in gastrointestinal contents. For both rodent species, it was done biometry of stomach, foregut, hindgut, and cecum and only Calomys tener was tested in relation to seasonality on diet and digestive tract morphology. For Necromys lasiurus, the consumption of animals (100%) was greater than plants (31%). For Calomys tener, plants were more frequent (92%) than animals (71%). It was not found seasonal variation in the composition, richness, or abundance of items on diet and it was not detected sexual or seasonal differences in body size and digestive tract as well. So, it was not possible to verify the existence of phenotypic flexibility on digestive tract. All samples from G. agilis had animal material and only 25% had plant material. Hymenoptera and Isoptera appeared as the most frequent and abundant taxons on the diet of G. agilis, C. tener and N. lasiurus. These results agree with the abundance of these preys in the Cerrado. Lutreolina crassicaudata consumed 64% of invertebrates, 27% of vertebrates and 9% of plant material. Dipteran maggots (Sarcophagidae) were found in association with vertebrates indicating that these items were consumed as carrion. For all species, fruits were the most frequent plant items. The well preservation of seeds suggests that studied species are potential dispersers, rather than seed predators. The studied species may be classified as omnivorous and probably opportunists. Necromys lasiurus and G. agilis have insectivorous-omnivorous habits, with domain of invertebrates on diet. Calomys tener can be considered herbivorous-omnivorous due to predominancy of plant material (mainly fruits) on its diet. Lutreolina crassicaudata uses necrophagy strategy instead of predation as it was supposed in preview studies on its feeding habits.